X-ray structures of two forms of the antibiotic oligomycin A: an inhibitor of ATP synthase. (May 2013) - Palmer, Rex A; Ladd, Mark; Howlin, Brendan; Lisgarten, David R
Background: Corrections to the chemical and x-ray structures of two forms of the antibiotic oligomycin A are presented: the original and best known, form (E), from Streptomyces diastatochromogenes, and a new form (C) from Streptomyces diastaticus .Method: The crystal structures are isomorphous, crystallizing in space group P 21 21 21, with Z = 4[C45 H73 O11 .CH3 OH] per unit cell. Oligomycin A(E) refined with R1 = 0.0734, using Cu Kα x-radiation; and for Oligomycin A(C) R1 = 0.0651 using Mo Kα x-radiation.Conclusion: Serious corrections to the previously published structure of oligomycin A(C) are discussed and implemented. As a supplementary study geometry optimization of side group R4 of oligomycin A(E) was undertaken and achieved by energy minimization. These additional results clearly confirm the delocalization in this region observed in both x-ray structures. This result is contrary to the generally accepted formulation. Knowledge of the correct structures is important to those involved in the study and applications of the pharmacological and biological properties of these materials.